Penerapan Praktek dan Teori Akuntansi Syariah Berdasarkan Prinsip Syariah - Muammar Khaddafi; Nuriani Nuriani; Ria Rama Sari; Nakita Sisilia; Nia Nazwa Aulia Pane; Athaya Hargita (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Sharia accounting is Islamic-based accounting that is based on the Quran and al-Hadith as well as ijma' ulama. Advances in the field of Indonesian accounting are recognized by Islamic accounting practices, which is also known as sharia accounting. The concept of sharia accounting describes the teachings of Islam, which influence all aspects of human life, including economics and accounting. The objective of this article is to explain the differences between the principles of conventional accounting and shariah accounting. To achieve this objective, this article uses the literature study method. All information and data in this paper are taken from scientific journals, books, and the internet. The results of the study show that shariah accounting is actually better in many ways than conventional accounting because it describes the conditions of the application of the principles of shariah and conventional accounting.